Photonic cancer nanomedicine using the near infrared-II biowindow enabled by biocompatible titanium nitride nanoplatforms - Wang, Chunmei; Dai, Chen; Hu, Zhongqian; Li, Hongqiang; Yu, Luodan; Lin, Han; Bai, Jianwen; Chen, Yu (Nanoscale horizons, 2019)
Light-activated photoacoustic imaging (PAI) and photothermal therapy (PTT) using the second near-infrared biowindow (NIR-II, 1000-1350 nm) hold great promise for efficient tumor detection and diagnostic imaging-guided photonic nanomedicine. In this work, we report on the construction of titanium nitride (TiN) nanoparticles, with a high photothermal-conversion efficiency and desirable biocompatibility, as an alternative theranostic agent for NIR-II laser-excited photoacoustic (PA) imaging-guided photothermal tumor hyperthermia. Working within the NIR-II biowindow provides a larger maximum permissible exposure (MPE) and desirable penetration depth of the light, which then allows detection of the tumor to the full extent using PA imaging and complete tumor ablation using photothermal ablation, especially in deeper regions. After further surface polyvinyl-pyrrolidone (PVP) modification, the TiN-PVP photothermal nanoagents exhibited a high photothermal conversion efficiency of 22.8% in the NIR-II biowindow, and we further verified their high penetration depth using the NIR-II biowindow and their corresponding therapeutic effect on the viability of tumor cells in vitro . Furthermore, these TiN-PVP nanoparticles were developed as a contrast agent for NIR-II-activated PA imaging both in vitro and in vivo for the first time and realized efficient photothermal ablation of the tumor in vivo within both the NIR-I and NIR-II biowindows. This work not only provides a paradigm for TiN-PVP photothermal nanoagents working in the NIR-II biowindow both in vitro and in vivo , but also proves the feasibility of PAI and PTT cancer theranostics using NIR-II laser excitation. Titanium nitride nanoparticles with high photothermal-conversion efficiency and desirable biocompatibility have been constructed as an alternative theranostic agent for NIR-II laser-excited photoacoustic imaging-guided photothermal tumor hyperthermia.